2020
DOI: 10.1038/s41416-020-01111-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing detects human papillomavirus (HPV) in cervical cancers negative for HPV by PCR

Abstract: Background Human papillomavirus (HPV) is a necessary cause of cervical cancer, although some invasive cervical cancers may test negative by HPV PCR. We previously requested all invasive cervical cancers in Sweden during 10 years and subjected them to PCR. We also optimised methods for deep sequencing of formalin-fixed paraffin-embedded samples. Methods Using Novaseq 6000, we simultaneously sequenced total DNA and cDNA from 392 HPV PCR-negative cervical cancers. Non-huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…This is in agreement with a meta‐analysis by Li et al, who reported a proportion of 0.5% of HPV73 among 12 588 invasive cancers 27 . However, the prevalence of HPV73 in cancers appears to vary between regions and HPV73 was ranked as the fourth most common type in the Oceania region based on data published from 1990 to 2010, 27 and was the ninth most common type among cervical cancer in Sweden during 2002 to 2011 26 . Additionally, Wallin et al demonstrated that the population‐based HPV 73 seroprevalence in Sweden was 14% 28 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in agreement with a meta‐analysis by Li et al, who reported a proportion of 0.5% of HPV73 among 12 588 invasive cancers 27 . However, the prevalence of HPV73 in cancers appears to vary between regions and HPV73 was ranked as the fourth most common type in the Oceania region based on data published from 1990 to 2010, 27 and was the ninth most common type among cervical cancer in Sweden during 2002 to 2011 26 . Additionally, Wallin et al demonstrated that the population‐based HPV 73 seroprevalence in Sweden was 14% 28 …”
Section: Discussionsupporting
confidence: 90%
“…At present, HPV73 is classified as possibly carcinogenic 2 . A mean HPV73‐prevalence of 0.62% (76/16027, range 0.35%‐15%) was observed by compiled results from six studies of invasive cervical cancer 2,10,23‐26 . This is in agreement with a meta‐analysis by Li et al, who reported a proportion of 0.5% of HPV73 among 12 588 invasive cancers 27 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The remaining "other" histological types of cervical cancers that we did not identify in this study typically constitute <4% of cervical cancers. 24 Two hundred cases did not have a cervical sample with an HPV analysis prior to diagnosis and were excluded. Altogether 319 cases with 1424 samples were identified.…”
Section: Study Populationmentioning
confidence: 99%
“…Based on the official PV nomenclature, PV’s taxonomic ranking is set according to the similarity of the highly conserved full-length L1 genes at the 60% nucleotide sequence similarity for genera, 70% for species and 90% for types [ 6 , 7 ]. With 224 human (HPV) and 215 animal PV types currently characterized and officially recognized, Papillomaviridae is one of the largest viral families infecting vertebrates [ 8 , 9 ]. In addition, complete PV genome sequences annotated with clinical and biochemical data that are readily available make PVs an attractive research model for study of the evolution of pathogen-host interactions [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%